Illness prevalence rate in Tibet, China: data from the 2018 National Health Service Survey - Rendan Deng; Labasangzhu; Zhaxideji; Guihua Wang; Peiwei Hong; Jiaqi Li; Qiwen Li; Yang Wan; Hai Xiong (BMC, 2020)
Abstract Background Tibet is located in the high-altitude area of Southwest China, where the health level is influenced by specific factors such as the natural environment and living habits. However, there has been little research that has focused on Tibetan health conditions. The two-week prevalence rate is an important indicator of the health level of residents. The purpose of this study was to understand the health status of the residents and the health service needs in Tibet. Methods The two-week prevalence rate was calculated using data from a population of 10,493 individuals aged 15 and above that was obtained from the 2018 Sixth National Health Service Survey of Tibet. We initially analysed the types and associated factors of two-week illnesses in Tibetan. The influencing factors for the two-week prevalence rate in Tibet were determined by multivariate logistic regression analysis. Subsequently, we assessed the severity of two-week illnesses by calculating the average days of the duration of the disease, the days of being bedridden and the days of being off work. Results The two-week illness prevalence rate was 20.1% in Tibet. Digestive system diseases were frequent, and hypertension was the most common disease. According to the multivariate logistic regression analysis, the two-week prevalence rate was associated with gender, age, residence, marital status, and employment status. In addition, the severity of two-week illnesses differed among the residents. Conclusion This study identified that health service needs have increased in Tibet and that the health status of the local residents needs to be improved. Moreover, hypertension has become a major health hazard for the residents and should be considered in the utilization of health services.